Refined diagnostic criteria for bone marrow mastocytosis: a proposal of the European competence network on mastocytosis - Zanotti, Roberta; Bonifacio, Massimiliano; Lucchini, Giuseppe; Sperr, Wolfgang R.; Scaffidi, Luigi; van Anrooij, Björn; Oude Elberink, Hanneke NC; Rossignol, Julien; Hermine, Olivier; Gorska, Aleksandra; Lange, Magdalena; Hadzijusufovic, Emir; et al. (Leukemia, 2022)
In the current classification of the World Health Organization (WHO), bone marrow mastocytosis (BMM) is a provisional variant of indolent systemic mastocytosis (ISM) defined by bone marrow involvement and absence of skin lesions. However, no additional diagnostic criteria for BMM have been proposed. Within the registry dataset of the European Competence Network on Mastocytosis, we compared characteristics and outcomes of 390 patients with BMM and 1175 patients with typical ISM. BMM patients were significantly older, predominantly male, had lower tryptase and lower burden of neoplastic mast cells, and displayed a higher frequency of allergic reactions, mainly triggered by Hymenoptera, than patients with typical ISM. The estimated 10-year progression-free survival of BMM and typical ISM was 95.9% and 92.6%, respectively. In BMM patients defined by WHO-based criteria, the presence of one B-Finding and tryptase level ≥125 ng/mL were identified as risk factors for progression in multivariate analyses. BMM patients without any of these risk factors were found to have better progression-free survival (p < 0.05) and better overall survival (p < 0.05) than other ISM patients. These data support the proposal to define BMM as a separate SM variant characterized by SM criteria, absence of skin lesions, absence of B-Findings, and tryptase levels <125 ng/mL.
Published online: 20 September 2021
Gesehen am 25.05.2023